THE AGE OF RECOMMENDATION: behaviors turned into sales - Furia, Fábio Augusto; Bruno, Diego Renan (Revista Interface Tecnológica, 2023)
Social changes are inherent to the time and space in which they occur, and there are several factors that can contribute to their change. In this context, the way of consuming content on the internet has suffered, impacting the way these materials are presented to consumers, trying to personalize the user's consumption experience as much as possible. Today, to make a sale, it is necessary to adapt to the lifestyle of the target audience. As a result, technological phenomena emerge in the virtual environment that help bring consumers and providers closer together. In this article, we will address switches known as pixels, which work as habit trackers, playing a fundamental role in obtaining data and transforming it into information for creating consumption in their own suggestion networks.
Keywords: Suggestion Networks; Social Media; Lifestyle; Technology; Digital Marketing